Comparison of senescence-associated miRNAs in primary skin and lung fibroblasts - Holly, A.C.; Grellscheid, S.N.; van de Walle, P.; Dolan, D.; Pilling, L.C.; Daniels, D.J.; von Zglinicki, T.; Ferrucci, L.; Melzer, D.; Harries, L.W. (Biogerontology, 2015)
MicroRNAs are non-coding RNAs with roles in many cellular processes. Tissue-specific miRNA profiles associated with senescence have been described for several cell and tissue types. We aimed to characterise miRNAs involved in core, rather than tissue-specific, senescence pathways by assessment of common miRNA expression differences in two different cell types, with follow-up of predicted targets in human peripheral blood. MicroRNAs were profiled in early and late passage primary lung and skin fibroblasts to identify commonly-deregulated miRNAs. Expression changes of their bioinformatically-predicted mRNA targets were then assessed in both cell types and in human peripheral blood from elderly participants in the InCHIANTI study. 57/178 and 26/492 microRNAs were altered in late passage skin and lung cells respectively. Three miRNAs (miR-92a, miR-15b and miR-125a-3p) were altered in both tissues. 14 mRNA targets of the common miRNAs were expressed in lung and skin fibroblasts, of which two demonstrated up-regulation in late passage skin and lung cells (LYST; p = 0.02 [skin] and 0.02 [lung] INMT; p = 0.03 [skin] and 0.04 [lung]). ZMPSTE24 and LHFPL2 demonstrated altered expression in late passage skin cells only (p = 0.01 and 0.05 respectively). LHFPL2 was also positively correlated with age in peripheral blood (p value = 6.6 × 10−5). We find that the majority of senescence-associated miRNAs demonstrate tissue-specific effects. However, miRNAs showing common effects across tissue types may represent those associated with core, rather than tissue-specific senescence processes.
EPrint Processing Status: DRO Team waiting for author to provide full text
Keywords: Cellular senescence; microRNA; Tissue specificity; Gene expression.